Aplicación de la teoría de Bruner para propiciar el aprendizaje de matemáticas en décimo año de educación general básica del colegio Víctor Proaño Carrión del cantón Riobamba, durante el año lectivo, 2012 - 2013 - Paguay, Milton (2016)
The present work is an alternative designed and executed alternative from the point of view of the theory of Bruner and its application in the process of learning, especially mathematics. Lead the learner to develop their ability to solve problems with the student to consider elements such as attitude, support, motivation and practice. Given this problem, produce their proposals to improve methods of learning and support this can be found in discovery learning, therefore I suggest the correct application of the theory of Bruner. Qualitative research in scientific method was used because it is a systematic rational and logical process through which from observation and definition of the problem. As the average level is satisfactory to apply the theory of Bruner exceeds 70%. Establishes the framework taking works of various authors for the construction of scientific theory, the methodological framework stands explaining the research design, the population of 40 children, is used as technical survey and observation as tools guide questionnaire and observation sheet, allowing these results. Perform data processing using charts and graphs in cakes, explaining through an analysis and interpretation of each of the answers given, the conclusions and recommendations that were reached to feed research a tutorial is designed arises.